A green approach to constructing multilayered nanocoating for flame retardant treatment of polyamide 66 fabric from chitosan and sodium alginate. (15th June 2017) - Kumar Kundu, Chanchal; Wang, Wei; Zhou, Shun; Wang, Xin; Sheng, Haibo; Pan, Ying; Song, Lei; Hu, Yuan
Highlights: A flame retardant nanocoating made from all bio-masses was deposited on PA66 fabric. Sodium alginate was oxidized in order to enhance the durability of the nanocoating. A maximal reduction of 24% in pHRR was achieved for PA66 with 5 QL deposition. The presence of nanocoating suppressed melt-dripping of PA66 fabric during combustion. Abstract: Green polyelectrolytes including chitosan (CS), phytic acid (PA) and oxidized sodium alginate (OSA) were deposited on polyamide 66 (PA66) fabrics in a quadralayer (QL) fashion like (CS-PA-CS-OSA)n (where "n" denotes the number of quadra layers) via layer-by-layer (LbL) assembly to improve the flame retardant property. In the vertical burning test, the PA66 fabric with 10 and 15 QL depositions could stop the melt-dripping. Cone calorimetry results showed that a maximum reduction (24%) in the peak heat release rate was achieved for the PA66 fabric with 5 QL depositions. Thermogravimetric analysis indicated that the presence of the polyelectrolytes catalyzed the degradation pathway of virgin PA66 fabric where the initial decomposition temperature was reduced and the char yield was enhanced for all the coated fabrics significantly. Moreover, UV–vis spectroscopy demonstrated that the use of OSA could improve the durability of such a multilayered nanocoating.